# Elimination method using addition and subtraction4x-2y=-1 and -4x+4y=-2

(-1,-3/2)

Step-by-step explanation:

4x-2y=-1

-4x+4y=-2

Add these two equations together to elimianate x

4x-2y=-1

-4x+4y=-2

2y = -3

Divide by 2

2y/2 =-3/2

y = -1.5

Now we need to find x

4x-2y =-1

4x -2(-1.5) = -1

4x +3 = -1

Subtract 3 from each side

4x+3-3 =-1-3

4x= -4

x=-1

2. Add -9x back into -3, you now have -4y=9x-3. Add +4 from y and now you are at y=9x-7 and this is your answer!!

I hope this helped! Brainliest? :) -Raven❤️

-5x-8y=-5

Step-by-step explanation:

add right sides of equation and even them with result of adding right sides of equation

4x-4y-9x-4y=-2-3

-5x-8y=-5

-5x-8y=-5

Step-by-step explanation:

add right sides of equation and even them with result of adding right sides of equation

4x-4y-9x-4y=-2-3

-5x-8y=-5

Step-by-step explanation:

You will subtract both numbers so

(4x - 4y) - (-9x - 4y) = 2+(-3)

4x + 9x = - 1

13x = - 1

x = - 1 /13

Next you have to put the value of x in equation no 1 and find the value of y

-24y = -4x - 2

Divide both sides by -24:-

y =1/6 x + 1/12